Asynchronous Android: harness the power of multi-core mobile processors to build responsive Android applications - Liles, Steve (Community experience distilled., 2013)
This title provides a step-by-step tutorial which explains how asynchronous tasks and handlers are used for performing multithreading with Android to improve the performance of Android applications. It also guides you through the concurrency constructs provided by the Android platform, illustrating the applications, benefits, and pitfalls of each.